2022
DOI: 10.1155/2022/8679511
|View full text |Cite|
|
Sign up to set email alerts
|

The Comparison of the Diagnostic Value of Left Atrial Pulmonary Vein Single-Phase and Dual-Phase Enhanced CT Scanning for Left Atrial Appendage Thrombosis and SEC in Patients with Atrial Fibrillation

Abstract: Objective. The accuracy of left atrial pulmonary vein CT enhanced single-phase and dual-phase scanning in the detection of left atrial appendage (LAA) thrombosis and spontaneous echo contrast (SEC) before radio frequency ablation was compared in atrial fibrillation patients, so as to optimize the scanning scheme. Methods. 78 patients with atrial fibrillation who were admitted to Cangzhou Central Hospital from October 2020 to September 2021 and underwent bilateral enhanced CT scan of left atrial pulmonary vein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Case groups: (1) True‐positive group: The CT showed a filling defect, and the TEE showed a positive result (Figures 1 and 2); (2) false‐positive group: The CT showed a filling defect, and the TEE showed a negative result (Figure 3); (3) true‐negative group: The CT showed no filling defect, and the TEE showed a negative result (Figure 4); (4) false‐negative group: The CT showed no filling defect, and the TEE showed a positive result. The CT has an extremely high negative predictive value in the detection of LAA thrombus and SEC (Guo et al, 2022; He et al, 2017; Tian et al, 2020; Yu et al, 2021), and only one CT false‐negative case occurred in this study; hence, the false‐negative result was not included in the statistics.…”
Section: Methodsmentioning
confidence: 86%
See 2 more Smart Citations
“…Case groups: (1) True‐positive group: The CT showed a filling defect, and the TEE showed a positive result (Figures 1 and 2); (2) false‐positive group: The CT showed a filling defect, and the TEE showed a negative result (Figure 3); (3) true‐negative group: The CT showed no filling defect, and the TEE showed a negative result (Figure 4); (4) false‐negative group: The CT showed no filling defect, and the TEE showed a positive result. The CT has an extremely high negative predictive value in the detection of LAA thrombus and SEC (Guo et al, 2022; He et al, 2017; Tian et al, 2020; Yu et al, 2021), and only one CT false‐negative case occurred in this study; hence, the false‐negative result was not included in the statistics.…”
Section: Methodsmentioning
confidence: 86%
“…Currently, radiofrequency catheter ablation (RFCA) has become a radical surgery for patients with AF, and thrombosis in LAA is an absolute contraindication of RFCA (Hindricks et al, 2021). Spontaneous echocardiographic contrast (SEC) represents blood flow stasis and the state before thrombosis (Wang et al, 2000); studies have demonstrated that LAA SEC in patients with AF has an equally important clinical significance as thrombus (Guo et al, 2022; Kosmalska et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%